2017
DOI: 10.1016/j.kjms.2017.10.002
|View full text |Cite
|
Sign up to set email alerts
|

Immune profiling of human prostate epithelial cells determined by expression of p38/TRAF‐6/ERK MAP kinases pathways

Abstract: The aim of the present work was to study the immune profiling of prostate epithelial cells by the expression of ASK‐1/p38 and Raf‐1/ERK MAP Kinases signaling pathways mediated by TRAF‐6. Immunohistochemical and Western blot analyses for TRAF‐6, ASK‐1, MEK‐6, p38, Raf‐1, MEK‐1, ERK‐1, ERK‐2 and PSA were carried out in 5 samples of normal prostate gland, 24 samples of BPH and 19 samples of PC. Immunoreaction to TRAF‐6 was found in the cytoplasm of epithelial cells of BPH and tumor cells of PC samples. For patien… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 37 publications
0
10
0
Order By: Relevance
“…To validate the above results from the Oncomine database, we examined the expression of HN1 in the matched cancer and paracancerous HCC tissues by real time PCR. Compared with the matched adjacent tissues, HN1 in 50% of the cancer tissues (7 out of 14) showed higher level, that in 35.7% of the cancer tissues (5 out of 14) were closer to its adjacent tissues, and that in 20% of the cancer tissues (2 out of 14) were lower than its adjacent tissues ( Figure 1C).…”
Section: The Expression Of Hn1 Is Up-regulated In Hcc Tissues and mentioning
confidence: 91%
See 2 more Smart Citations
“…To validate the above results from the Oncomine database, we examined the expression of HN1 in the matched cancer and paracancerous HCC tissues by real time PCR. Compared with the matched adjacent tissues, HN1 in 50% of the cancer tissues (7 out of 14) showed higher level, that in 35.7% of the cancer tissues (5 out of 14) were closer to its adjacent tissues, and that in 20% of the cancer tissues (2 out of 14) were lower than its adjacent tissues ( Figure 1C).…”
Section: The Expression Of Hn1 Is Up-regulated In Hcc Tissues and mentioning
confidence: 91%
“…Western blot was performed as previously described with modifications . Briefly, cells were lysed in RIPA lysis buffer, and the equal amounts of proteins were resolved with loading buffer.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…When RhoD expression was high, the MAPK pathway was activated, the residue of Tyr and Thr was phosphorylated, the ErK pathway was activated, and the phosphorylation levels of c-fos and c-jun increased. At the same time, the Smad 1 and Smad 5 also showed increased expression; thus, the oocyte differentiation and ovulation were induced [36][37][38].…”
Section: Discussionmentioning
confidence: 96%
“…MAPKs, including ERK1/2, JNK, and p38, have long been implicated in the regulation of gene expression, cell proliferation, cellular metabolism, cell migration, inflammatory, differentiation, and apoptosis. [41][42][43] Over-expression and phosphorylation of the MAPK signaling pathway may lead to increased cell proliferation and resistance to apoptosis. 44 A recent study reported that PDZ binding kinase, a serine-threonine kinase, accelerates cell apoptosis by activating the MAPK signaling pathway in nasopharyngeal carcinoma.…”
Section: Discussionmentioning
confidence: 99%